QUALIFIED SPECIALIST IN AGRICULTURE PERSONNEL SUPPORT AND CHANGES IN IT - Akhmedova Umidakhan; Vakhobov Shakhrukh (American Journals Publishing, 2024)
This article focuses on the issues of training specialists in the field of Agriculture in our republic after independence, including the Andijan region.
Keywords: Education law, personnel, specialty, agriculture, colleges